New spatial planning approaches to protect periurban agrarian spaces (Ciudades, 2017)
In Europe, the periurban agrarian spaces receive the highest urban pressure: between 1990 and 2000, the 77% new artificial uses grew upon agrarian areas. Analyzing the evolving objectives of the spatial planning in the European Union, becomes evident the minor significance gived to the agrarian systems. Neither this is consequence with the environmentalist discourse; nor is facing the scenario coming with the energy crisis, the global change and the depletion resource. Neither the Common Agricultural Policy helps to preserve periurban agrarian spaces which will play an important role in the future viability of our cities. The stablishment of adequate forms of protection, their reconsideration within the planning tools and the enhancement of agricultural activity would reduce the urban expectations, slowing down their transformation. The analysis of different European cases can provide interesting lessons on how to progress towards these goals.
Keywords: periurban agrarian spaces; urban pressure; protection; spatial planning; Europe